Bioprocessing analysis of Pyrococcus furiosus strains engineered for CO2‐based 3‐hydroxypropionate production. Issue 8 (11th June 2015) - Hawkins, Aaron B.; Lian, Hong; Zeldes, Benjamin M.; Loder, Andrew J.; Lipscomb, Gina L.; Schut, Gerrit J.; Keller, Matthew W.; Adams, Michael W.W.; Kelly, Robert M.
ABSTRACT Metabolically engineered strains of the hyperthermophile Pyrococcus furiosus (Topt 95–100°C), designed to produce 3‐hydroxypropionate (3HP) from maltose and CO2 using enzymes from the Metallosphaera sedula (Topt 73°C) carbon fixation cycle, were examined with respect to the impact of heterologous gene expression on metabolic activity, fitness at optimal and sub‐optimal temperatures, gas‐liquid mass transfer in gas‐intensive bioreactors, and potential bottlenecks arising from product formation. Transcriptomic comparisons of wild‐type P. furiosus, a genetically‐tractable, naturally‐competent mutant (COM1), and COM1‐based strains engineered for 3HP production revealed numerous differences after being shifted from 95°C to 72°C, where product formation catalyzed by the heterologously‐produced M. sedula enzymes occurred. At 72°C, significantly higher levels of metabolic activity and a stress response were evident in 3HP‐forming strains compared to the non‐producing parent strain (COM1). Gas–liquid mass transfer limitations were apparent, given that 3HP titers and volumetric productivity in stirred bioreactors could be increased over 10‐fold by increased agitation and higher CO2 sparging rates, from 18 mg/L to 276 mg/L and from 0.7 mg/L/h to 11 mg/L/h, respectively. 3HP formation triggered transcription of genes for protein stabilization and turnover, RNA degradation, and reactive oxygen species detoxification. The results here support the prospects of using thermally diverse sources of pathways and enzymes in metabolically engineered strains designed for product formation at sub‐optimal growth temperatures. Biotechnol. Bioeng. 2015;112: 1533–1543. © 2015 Wiley Periodicals, Inc.